Prognostic role of pre-procedural lung ultrasound in patients undergoing transcatheter aortic valve implantation - Guilherme Pinheiro Machado; Pedro Castilhos de Freitas Crivelaro; Gustavo Neves de Araujo; Guilherme Heiden Telo; Luiz Carlos Corsetti Bergoli; Marina Petersen Saadi; Julia Carvalho da Silva; Camila Porto Cardoso; Wagner Azevedo; Felipe Costa Fuchs; Marco Wainstein (Frontiers in Cardiovascular Medicine)
BackgroundTranscatheter aortic valve implantation (TAVI) is the preferred treatment for patients with severe aortic stenosis (AS) in patients >75 years. Lung ultrasound (LUS) has emerged as a noninvasive tool for assessing pulmonary congestion and risk stratification in cardiovascular disease, especially heart failure, however, its prognostic role in TAVI remains to be clarified. Therefore, our aim was to investigate the association between pre-procedural LUS findings and clinical outcomes in patients undergoing TAVI.MethodsWe conducted a prospective cohort study of 116 patients undergoing TAVI from 2021 to 2024. Lung ultrasound was performed immediately before the procedure. Patients were classified as having “wet lungs” (≥1 positive zone) or “dry lungs” (no positive zones). Exclusion criteria were lack of consent or absence of pre-procedural ultrasound assessment. The primary endpoint was a composite of all-cause mortality and heart failure hospitalization within 12 months. Secondary endpoints included VARC-2-defined complications.ResultsAmong 85 patients included in the final analysis the mean age was 80 ± 11 years, 51.8% were male, and 55 (64.7%) had wet lungs. Patients with wet lungs had higher STS-PROM scores (5.2% vs. 3.0%, p < 0.001), but there were no significant differences in the primary outcome (3.8% vs. 6.7%, p = 0.55). Moreover, procedural characteristics and complication rates were similar between groups.ConclusionsPre-procedural LUS was not associated with worse outcomes following TAVI. While LUS may reflect comorbidity burden, its isolated prognostic value in this setting appears limited.